Trypanocidal Activity of Smallanthus sonchifolius. Identification of Active Sesquiterpene Lactones by Bioassay-Guided Fractionation. - Frank, Fernanda Maria (2013)
In order to find novel plant-derived biologically active compounds against Trypanosoma cruzi, we isolated, from the organic extract of Smallanthus sonchifolius, the sesquiterpene lactones enhydrin (1), uvedalin (2), and polymatin B (3) by bioassay-guided fractionation technique. These compounds showed a significant trypanocidal activity against the epimastigote forms of the parasite with IC50 values of 0.84 μM (1), 1.09 μM (2), and 4.90 μM (3). After a 24 h treatment with 10 μg/mL of enhydrin or uvedalin, parasites were not able to recover their replication rate. Compounds 1 and 2 showed IC50 values of 33.4 μM and 25.0 μM against T. cruzi trypomastigotes, while polymatin B was not active. When the three compounds were tested against the intracellular forms of T. cruzi, they were able to inhibit the amastigote replication with IC50 of 5.17 μM, 3.34 μM, and 9.02 μM for 1, 2, and 3, respectively. The cytotoxicity of the compounds was evaluated in Vero cells obtaining CC50 values of 46.5 μM (1), 46.8 μM (2), and 147.3 μM (3) and the selectivity index calculated. According to these results, enhydrin and uvedalin might have potentials as agents against Chagas disease and could serve as lead molecules to develop new drugs.